ALTERNATIVE AND FLEXIBLE FORMS OF EMPLOYMENT: SITUATION IN CZECH REPUBLIC - Šmíd, Martin; Navrátilová, Sabina (Varazdin Development and Entrepreneurship Agency, 2017)
The paper deals with the legal options of using of alternative and flexible forms of employment in Czech Republic according to the legal frame given mainly by the Labour Code (Act No. 262/2006 Coll.). The theoretical approach in the paper is based on the principle of flexicurity combining the concept of flexibility and the concept of security of employment. The difference between flexibility and liberalization of labour law and the context of Industry 4.0 is also mentioned in the paper. Current situation and evolution of use of these alternative and flexible forms of employment is analysed in the paper; the analysis is focused on part-time jobs. The paper includes comparison of the situation in the neighboring countries (Germany, Austria, Slovakia and Poland). The conclusion is focused on limits of flexibility and liberalization of labour law and summarizes the benefits of alternative and flexible forms of employment and the possibilities of its higher usage in Czech labour law.
Alternativní a flexibilní formy zaměstnání: situace v České republice
Keywords: labour law; flexicurity; liberalization; employment; pracovní právo; flexikurita; liberalizace; zaměstnání